SEMANTIC ANALYSIS OF BLESSING WORDS IN ENGLISH AND UZBEK LANGUAGES - Norkobilova Nigora Uralovna (Bright Mind Publishing, 2026)
This article presents a semantic analysis of blessing words in the English and Uzbek languages. Blessing words constitute an important part of evaluative and expressive vocabulary, functioning as linguistic means of goodwill, benevolence, and positive wishes. The study investigates the semantic structure, functional features, connotative meanings, and linguocultural specificity of blessing words in both languages. A comparative approach is employed to identify universal semantic components and culture-specific characteristics of blessings.
Keywords: Blessing words, semantics, evaluative vocabulary, English language, Uzbek language, linguocultural analysis